The Use of Evidence in Humanitarian Decision Making - Stobaugh, Heather; Walker, Peter; Maxwell, Daniel; Darcy, James (Tufts Archival Research Center, 2014)
Abstract: The study is based around three main questions. First, how do decision makers in the humanitarian sector currently use information and analysis? Second, what factors, other than information and analysis, are influential in making decisions? Third, what would enable better-informed response decisions? In order to address these overarching questions, the study looks first at some of the main processes of decision-making in the humanitarian sector and the factors that appear to have most influence on decisions of different kinds. It goes on to look at the way information and analysis is currently generated in the humanitarian sector—both through formal and informal means—and related questions of relevance and credibility. These two topics are then brought together in addressing the question of the use of information by decision makers, and what might enable more informed and evidence-based response decisions.